Phototransduction Gene Expression and Evolution in Cave and Surface Crayfishes. (14th May 2018) - Stern, David B; Crandall, Keith A
Abstract: In the absence of light in caves, animals have repeatedly evolved reduced eyes and visual systems. Whether the underlying genetic components remain intact in blind species remains unanswered across taxa. The freshwater crayfish have evolved to live in caves multiple times throughout their history; therefore, this system provides an opportunity to probe the genetic patterns and processes underlying repeated vision loss. Using transcriptomic data from the eyes of 14 species of cave and surface crayfishes, we identify the expression of 17 genes putatively related to visual phototransduction. We find a similarly complete repertoire of phototransduction gene families expressed in cave and surface species, but that the expression levels of those transcripts are consistently lower in cave species. We find statistical support for episodic positive selection, increased and decreased selection strength in caves, depending on the gene family. Analyses of gene expression evolution suggest convergent and possibly adaptive downregulation of these genes across eye-reduction events. Our results reveal a combination of evolutionary processes acting on the sequences and gene expression levels of vision-related genes underlying the loss of vision in caves.